Al-Qur'an Literacy as an Effort to Shape Student Character at SMP Muhammadiyah 57 Medan - Silvia Febrianti (Yayasan Rahmat Islamiyah, 2023)
While the purpose of this study is an effort to shape the character of students and form understanding in reading the Koran. In this article, the method used by the author is a qualitative method with interviews and observations of teachers and students of grade 7 SMP Muhammadiyah 57 Medan. Based on the results of interviews and observations made that al-Qur'an literacy activities as a positive habituation in schools are able to shape the character of students and improve the ability to read the Koran, this can be seen from students who have a polite, brave, creative attitude and are able to manage time and enthusiasm in participating in learning activities.